Fowler, J. D., Ranch and Residence, Willow Creek, San Luis Obispo County; Mayfield, B.F., Ranch and Residence, San Simeon Creek, San Luis Obispo Co., Cal.[On Same Plate] (1883)
Hand-tinted lithographs.